Identification of Weak Frequency Areas in Low Inertia Systems - Ignacio Ponce; Claudia Rahmann; Pouyan Pourbeik (IEEE Access)
The continued replacement of synchronous generators by converter-interfaced generators (CIG) is changing power systems dynamics worldwide. Regarding frequency stability, reduced system inertia is leading to larger and steeper frequency deviations, threatening system security in some regions of the world. Moreover, recent investigations have recognized that an uneven spatial distribution of inertia can significantly deteriorate the local rate of change of frequency and frequency oscillations. In this context, screening methods to identify weak frequency areas are one of the critical tools needed to successfully overcome the technical challenges of the energy transition. With the aim in mind, this paper proposes a systematic methodology to identify weak frequency areas. The main outcome is an offline tool that calculates a novel frequency strength indicator for each area called the Local Equivalent Effect of Inertia Index (LEEII). The indicator considers the spatial distribution of inertia and generation dispatch information along with some key technical characteristics of systems dominated by CIG. The tool is applied to the Chilean electricity system. The results, validated through time-domain simulations, allow identifying weak areas of the system that may experience frequency stability issues. Moreover, the proposed LEEII helps to define sufficient conditions for ensuring a secure operation from a frequency perspective.